2009
DOI: 10.1038/nsmb.1554
|View full text |Cite
|
Sign up to set email alerts
|

Transient ribosomal attenuation coordinates protein synthesis and co-translational folding

Abstract: Clustered codons that pair to low-abundance tRNA isoacceptors can form slow-translating regions in the mRNA and cause transient ribosomal arrest. We report that folding efficiency of the Escherichia coli multidomain protein SufI can be severely perturbed by alterations in ribosome-mediated translational attenuation. Such alterations were achieved by global acceleration of the translation rate with tRNA excess in vitro or by synonymous substitutions to codons with highly abundant tRNAs both in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
534
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(548 citation statements)
references
References 49 publications
14
534
0
Order By: Relevance
“…There are many features that can contribute to the pausing and processivity of the synthetic machinery as it translates its template mRNA and it is becoming apparent that this is not as simple as, or restricted to, the secondary structure of the RNA ahead of the ribosome. Pausing may also be regulated by the abundance of charged tRNA, the number of consecutive codons for the same amino acid 2 , the charge of the newly synthesised peptide, folding and secondary structure of the peptide fragment within the exit tunnel 3, 4 , the influence of non-canonical wobble bases in codon:anticodon pairing 5 or by chemical damage of mRNAs or their degradation such that they lack a stop codon. Transient accumulation of ribosomes can also be observed at sites of translation initiation, whilst ribosomes are localising to particular subcellular locations 6 or during recruitment of chaperones or regulatory factors 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many features that can contribute to the pausing and processivity of the synthetic machinery as it translates its template mRNA and it is becoming apparent that this is not as simple as, or restricted to, the secondary structure of the RNA ahead of the ribosome. Pausing may also be regulated by the abundance of charged tRNA, the number of consecutive codons for the same amino acid 2 , the charge of the newly synthesised peptide, folding and secondary structure of the peptide fragment within the exit tunnel 3, 4 , the influence of non-canonical wobble bases in codon:anticodon pairing 5 or by chemical damage of mRNAs or their degradation such that they lack a stop codon. Transient accumulation of ribosomes can also be observed at sites of translation initiation, whilst ribosomes are localising to particular subcellular locations 6 or during recruitment of chaperones or regulatory factors 7 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been demonstrated that the tertiary folding of protein domains can begin during their synthesis by the ribosome 7,15,19,31 . Translation introduces an additional process that can influence nascent protein folding; hence, the kinetic equations describing protein folding have recently been expanded to account for the impact of codon translation rates 10,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimentalists have found that the introduction of presumably slow-translating synonymous substitutions often increases the extent of co-translational protein folding as reflected by the enzymatic activity 42 or resistance to proteases 31 of nascent proteins. For example, a domain in SufI lost resistance to protease degradation when two rare codons were replaced with common codons, suggesting faster elongation kinetics in the mutant transcript provide that domain insufficient time to co-translationally fold 31 . Similarly, it was found that optimizing codon usage in the N-terminal 164 codons of the Neurospora clock protein frequency (FRQ) was sufficient to decrease its ability to associate with the protein WC-2 by 60% 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising because translation speed is unlikely to be the only selective force acting on codon selection. A number of other genomic parameters including GC-contents (Knight et al, 2001), mRNA folding (Tuller et al, 2011;Bentele et al, 2013), co-translation protein folding (Zhang et al, 2009;Xie et al, 1998;Mukhopadhyay et al, 2007) are also relevant. Moreover, even if translation speed were the only adaptive force, it would be very difficult to maintain a globally optimised genome in the face of continuous mutational pressure.…”
Section: Local and Global Effectsmentioning
confidence: 99%